2021
DOI: 10.3390/brainsci11020279
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Sodium Calcium Exchanger Suppresses Alcohol Withdrawal-Induced Seizure Susceptibility

Abstract: Calcium influx plays important roles in the pathophysiology of seizures, including acoustically evoked alcohol withdrawal-induced seizures (AWSs). One Ca2+ influx route of interest is the Na+/Ca2+ exchanger (NCX) that, when operating in its reverse mode (NCXrev) activity, can facilitate Ca2+ entry into neurons, possibly increasing neuronal excitability that leads to enhanced seizure susceptibility. Here, we probed the involvement of NCXrev activity on AWS susceptibility by quantifying the effects of SN-6 and K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…We have previously reported that systemic administration of NCX rev activity inhibitors suppressed AWSs in adult male rats; these ndings suggest NCX remodeling, at least in the IC, the site of AWS initiation [32]. Here, we explored a potentially novel mechanism underlying AWSs-the upregulation of NCX1 in the IC.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We have previously reported that systemic administration of NCX rev activity inhibitors suppressed AWSs in adult male rats; these ndings suggest NCX remodeling, at least in the IC, the site of AWS initiation [32]. Here, we explored a potentially novel mechanism underlying AWSs-the upregulation of NCX1 in the IC.…”
Section: Discussionmentioning
confidence: 92%
“…Of interest is the Na + / Ca 2+ exchanger (NCX), a membrane transporter, when operating in its reverse mode (NCXrev), is also an essential pathway for Ca 2+ entry into neurons and may play a role in the pathophysiology of seizures, including of AWSs [27][28][29][30][31]. Accordingly, blocking the reverse mode activity of NCX (NCX rev ) suppressed acoustically evoked AWSs [32]. Three NCX isoforms, including type 1 (NCX), type 2 (NCX2), and type 3 (NCX3), are expressed in the brain, and each isoform has a distinct molecular expression pattern and pharmacological sensitivity [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…The directionality of the passage of ions through the NCX is dependant on ion concentrations and the membrane potential of the astrocyte ( Khananshvili, 2014 ). Generally, NCX function is thought to facilitate seizures given the observation that pharmacological inhibition of NCX function ( Saito et al, 2009 ) and downregulation of NCX expression both have anticonvulsant effects ( Akinfiresoye et al, 2023 ; Newton et al, 2021 ; Saito et al, 2009 ). Experiments utilizing pharmacological inhibition specific to the reverse function of the NCX (in which Ca 2+ enters the cell) indicate that it is this aspect of NCX function which confers its proconvulsant properties ( Akinfiresoye et al, 2023 ; Martinez and N’Gouemo, 2010 ).…”
Section: Gliotransmission and The Tripartite Synapsementioning
confidence: 99%
“…Calcium influx plays important role in alcohol-withdrawal-induced seizures. Newton J et al (Newton et al, 2021) reported using pharmacologic blocker (SN-6) to prevent calcium from flowing into neurons, which suppressed the occurrence of withdrawalinduced seizures in adult Sprague-Dawley rats, SN-6 also markedly reduced the seizure severity. Calcium ions are essential to many nervous system functions.…”
Section: Discussionmentioning
confidence: 99%